Prevalence, aetiology and management of ureteric injuries in Mulago National Referral Hospital, Kampala, Uganda - Obore, Susan; Barageine, Justus (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the prevalence, aetiology and management of ureteric injuries in the Urogynecology unit of Mulago National Referral Hospital. Methods: Records of patients operated for ureteric injuries from January 2005 to December 2017 were reviewed. The type of operations associated with the injury, duration of injury and mode of management of the injuries was reviewed. Results: There were 140 patients operated for ureteric injuries during the study period and this constituted 9.1% of all operations for urinary incontinence. Records of 125 patients were reviewed. The mean age of the patients at admission was 30.9 years and the mean duration of leakage was 19.8 months. In 100 (80%) of patients the leakage followed delivery and 25(20%) followed gynecological operations. Most of the patients 80 (64%) presented with vaginal leakage of urine/fistula while 7(5.6%) presented with transection of the ureter. The commonest site of injury was the left ureter (73.7%) and 17(13.6%) had bilateral injury. All the patients were managed by surgical repair with a success rate of 90.6%. Conclusions: Iatrogenic ureteric injuries following c/section and c/section hysterectomy are a cause of morbidity and effort should be made to improve on surgical skills and ensure early recognition of injury. Keywords: fistula,iatrogenic, ureter injury